2014
DOI: 10.1104/pp.114.237388
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic Acid and Its Precursor 12-Oxophytodienoic Acid Control Different Aspects of Constitutive and Induced Herbivore Defenses in Tomato

Abstract: The jasmonate family of growth regulators includes the isoleucine (Ile) conjugate of jasmonic acid (JA-Ile) and its biosynthetic precursor 12-oxophytodienoic acid (OPDA) as signaling molecules. To assess the relative contribution of JA/JA-Ile and OPDA to insect resistance in tomato (Solanum lycopersicum), we silenced the expression of OPDA reductase3 (OPR3) by RNA interference (RNAi). Consistent with a block in the biosynthetic pathway downstream of OPDA, OPR3-RNAi plants contained wild-type levels of OPDA but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 139 publications
(189 reference statements)
3
107
3
Order By: Relevance
“…After successful fertilization, NO and JA are likely also important during embryo development (Supplemental Fig. S9; Goetz et al, 2012) and defense (Bosch et al, 2014), as indicated by recent studies in tomato (Solanum lycopersicum). Therefore, it is conceivable that our findings have important implications for other plant species and conditions in which NO and/or JA act as signaling components: in the case of peroxisomal NO during abiotic stress in roots (Corpas et al, 2009;Corpas and Barroso, 2014a) and in the case of JA during herbivory/wounding or plant-pathogen interactions.…”
Section: Discussionmentioning
confidence: 78%
“…After successful fertilization, NO and JA are likely also important during embryo development (Supplemental Fig. S9; Goetz et al, 2012) and defense (Bosch et al, 2014), as indicated by recent studies in tomato (Solanum lycopersicum). Therefore, it is conceivable that our findings have important implications for other plant species and conditions in which NO and/or JA act as signaling components: in the case of peroxisomal NO during abiotic stress in roots (Corpas et al, 2009;Corpas and Barroso, 2014a) and in the case of JA during herbivory/wounding or plant-pathogen interactions.…”
Section: Discussionmentioning
confidence: 78%
“…We chose not to review the development of trichomes in Arabidopsis, as this has been thoroughly reviewed (Balkunde et al, 2010;An et al, 2011;Tominaga-Wada et al, 2011;Pattanaik et al, 2014;Matías-Hernández et al, 2016). Unlike the situation of Arabidopsis, which contains a single type of unicellular, nonglandular trichome, our understanding of the molecular genetic aspects of glandular trichome development is still in its infancy but currently improving due to recent progress in omics and genomeediting technologies as well as to a growing focus from several research teams to characterize this process in different plant species (Li et al, 2004;Dai et al, 2010;Bosch et al, 2014;Bergau et al, 2015;Liu et al, 2016). The (draft) genome sequences of a number of plant species with glandular trichomes are now available.…”
Section: A Detailed Understanding Of Glandular Trichome Initiation Anmentioning
confidence: 99%
“…In this respect, some phytohormones, especially jasmonate (JA) and possibly GAs, elicit glandular trichome development via signaling cascades and the activation of trichome-specific transcriptional regulators (Li et al, 2004;Koo and Howe, 2009;Bose et al, 2013;Bosch et al, 2014;Tian et al, 2014;Liu et al, 2017;Yan et al, 2017). In Mentha arvensis, exogenous application of GA resulted in a moderate increase in trichome density and diameter of the gland, suggesting a positive, although moderate, effect of GA on trichome initiation and development in mint (Bose et al, 2013).…”
Section: A Detailed Understanding Of Glandular Trichome Initiation Anmentioning
confidence: 99%
“…Transgenic tomato (Solanum peruvianum) cell lines were generated by particle bombardment as described (Cedzich et al, 2009;Pickel et al, 2010). Transgenic tomato plants were generated by Agrobacterium tumefaciens-mediated transformation as described (Bosch et al, 2014).…”
Section: Expression Of Sl3-mmp Variants In Transgenic Cell Cultures Amentioning
confidence: 99%
“…The entire expression cassette comprising the CaMV 35S promoter, Sl3-MMP-HP, and the OCS terminator was cut out with NotI and transferred into pART27 (Gleave, 1992). Transgenic tomato plants were generated by A. tumefaciens-mediated transformation as described (Bosch et al, 2014). Stable integration of the transgene and the independence of transformation events were confirmed by Southern-blot analysis.…”
Section: Silencing Of Sl-mmps By Rnaimentioning
confidence: 99%